Agribusiness Innovation through TVET: Role of Business Incubation in Nepal - Bhandari, Ramesh (Journal of Technical and Vocational Education and Training, 2026)
Although the agriculture sector is the backbone of rural economy in Nepal, the agricultural productivity is low in rural areas coupled with limited opportunities for value addition. This has forced the youths to migrate abroad for employment. The Technical and Vocational Education and Training (TVET) system operating in Nepal has provided thousands of youths with technical skills. The education provided to the youths with a focus on entrepreneurial skills has, however, been weak. This study has reviewed the aspects of business incubation and examined how it can stimulate innovation and strengthen rural transformation in rural agricultural businesses. It has also reviewed the evidence from various agricultural policies of the country, innovation methods and incubation models operated in other countries. The study has identified business incubation as a mechanism to link skills with enterprise creation. Incubation services, such as market linkage development, business development support, will help in empowering trainees to become agricultural entrepreneurs. It has been concluded that the agricultural value chain can contribute to development and inclusive economic growth. Innovation centers, various support funds and national incubation frameworks should be established at various levels to formalize this approach in agribusiness. Moreover, it is imperative to transform Nepal's skills ecosystem into a vehicle for agribusiness innovation and rural prosperity.